Analisis Implementasi Rencana Strategis (Renstra) Dinas Pertanian dan Peternakan Kabupaten Bangkalan Tahun 2013 – 2018 - Badrut Tamam; Mohamad Djasul (LPPM Universitas Trunojoyo Madura, 2016)
The purpose of this study was to determine the process of implementation of the Strategic Plan for Agriculture and Livestock Bangkalan 2013-2018 next to know how to evaluate the implementation of the Strategic Plan for Agriculture and Livestock Bangkalan 2013 - 2018. In this study using qualitative research methods, sources of data used are primary data and secondary data, data collection techniques used were observation, interviews and documentation. The technique of data analysis using a model of Miles and Huberman. Results from this study is the process of implementation of the Strategic Plan, namely Bangkalan Dispertanak: 1) regulatory approval stages, namely the decision on approval regulations Regent No. 2 th 2013 on RPJMD Bangkalan the reference Strategic Plan, 2) Further Decision ratified Head of Strategic Plan 2013-2018 Year Dispertanak Bangkalan District, 3) Implementation of the Strategic Plan into the annual working plan, then set up the Annual Work Plans (RKT) and performance agreements (PK), 4) Implementation of the Strategic Plan by stakeholders, 5) the target group for running programs. 6) The impact of the results that have been implemented well or not, 7) Evaluation of policies or legislation to planning further development. Then need to be made as an implementation framework that has been presented Mr. Ridwan as Head of programming that the implementation framework Dispertanak Bangkalan include: Resources, Governance, Socialization, Information Systems, Coordination, and the Top Management Commitment. The conclusions of this final project is generally Dispertanak Bangkalan have conducted in accordance with the Strategic Plan of the stages that have been determined and implemented too well, as evidenced by the achievement of annual performance increases with the average number of achievements in 2013 amounted to 98.04%, 2014 amounted to 95.28%, and 2015 by 111%. Process Evaluation of the Strategic Plan, namely: 1) monitoring and control of monthly and quarterly programs, 2) an annual performance evaluation through LAKIP and SAKIP, 3) evaluation of the performance of the middle period of the Strategic Plan through the attainment of performance Dispertanak, and 4) the final evaluation of the Strategic Plan period.